Leveraging Social Media for Cultural Preservation: Promoting Traditional Minangkabau Arts in the Digital Era - Diego Diego; Yayuk Lestari; Sarmiati Sarmiati; Vitania Yulia; Farhan Muwaffaq (Penerbit Jurnal Indonesia, 2024)
This study discusses how the Siliah Galanggang Arts Community utilizes social media to maintain and promote Minangkabau traditional arts. Using media ecology theory, this research analyzes the interactions and social media ecosystem within the community and its impact on the existence of traditional culture. A qualitative research method with a descriptive approach was used in this study, involving observation, interviews, and documentation. The results show that social media plays a crucial role in sustaining traditional culture through various digital platforms. With approximately 200 members, this community utilizes a social media ecosystem comprising Instagram, WhatsApp, and TikTok to expand reach and promote traditional culture. Instagram is used as a visual documentation showcase, WhatsApp for intensive communication, and TikTok to attract a global audience. Through this interconnected media ecosystem, the Siliah Galanggang Arts Community has successfully created an effective platform for interacting with the audience and promoting traditional arts. Support from local officials, collaboration with art enthusiasts, and participation in cultural festivals and social events strengthen the community’s presence. Challenges in funding and relevance in the digital era are addressed with innovative strategies and educational programs. With a long-term vision to establish a cultural center, this community is committed to preserving and developing Minangkabau cultural heritage through education, training, and active participation in cultural activities.